2018
DOI: 10.3390/en11092313
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism Analysis of Roadway Rockbursts Induced by Dynamic Mining Loading and Its Application

Abstract: Roadway rockbursts seriously restrict the safety production of coal mines; however, the interaction between dynamic loads and roadway surrounding rocks has not been fully considered in existing studies. A dynamic failure analysis model of anchoring supporting structures was established to analyze dynamic effects of stress waves. Taking a rockburst in LW402103 of the Hujiahe coal mine as the case, the theoretical model was well applied and verified. The static cumulative resistance Qs (210.5 kN) which was incur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…In the process of roadway excavation and working face mining, the phenomenon of roadway floor heave and rock burst is often accompanied. Especially after reaching deep mining, this kind of phenomenon becomes increasing prominent [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…In the process of roadway excavation and working face mining, the phenomenon of roadway floor heave and rock burst is often accompanied. Especially after reaching deep mining, this kind of phenomenon becomes increasing prominent [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…It is a type of dynamic disaster encountered in deep, hard rock underground engineering. With the expansion of the scale of deep underground engineering operations, rockbursts occur more frequently and with greater severity [8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Two rockburst examples are shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…It is a kind of dynamic instability geological disaster in that the elastic strain energy of the surrounding rock can be released suddenly and produces burst release, exfoliation, ejection, and even throw in the rock mass caused by the brittle failure of the excavation unloading during or after the excavation of the underground engineering in the high stress zone [9,10]. Studies have shown that rockburst generally occurs in underground engineering with hard brittle rock mass under high geostress conditions, and the occurrence process is short without obvious premonition [11][12][13][14]. Rockburst is becoming an important factor affecting the construction of deeply buried underground engineering.…”
Section: Introductionmentioning
confidence: 99%